The Cost and Efficiency of Distribution in the Soviet Union - Goldman, Marshall I. (Quarterly Journal of Economics, 1962)
I. Introduction, 437. — II. A comparison of Russian and American distribution markups, 438. — III. Significance of lower costs of distribution in the Soviet Union as a measure of productivity, 447. — IV. Conclusion, 452.